Career Decision-Making Profiles of Adolescents in Cyprus (European Journal of Teaching and Education, 2020)
The purpose of the present study is to examine the career decision-making profile of the adolescent students of the public high schools of Cyprus by applying the Career Decision-Making Profiles (CDMP) questionnaire of Gati, Landman, Davidovitch, Peretz-Asulin, & Gadassi (2010). The development of the CDMP suggests that an individual’s career decision making process can be better described by a multidimensional profile instead of a single decision-making style or a dominant characteristic. Using the data of 421 students, who were about to make a career choice, the results of the survey revealed eight dimensions for the Greek-Cypriot version of CDMP scale. The findings construct a multidimensional profile characterization of an individual’s career decision making processes: (1) “Information gathering and processing-Effort invested in the process”, (2) “Desire to please others-Dependence on others”, (3) “Speed of making the final decision”, (4) “Consulting with others”, (5) “Aspiration for an ideal occupation”, (6) “Locus of control”, (7) “Willingness to compromise”, (8) “Procrastination”. Using the T-test, we will discuss significant gender differences in the eight dimensions of the CDMP.